THE EVOLUTION OF MUNICIPAL BOND MARKET IN POLAND - Łękawa, Zofia (Ekonomika, 2011)
The Act of 29 June 1995 on Bonds has formally launched the development of a market for municipal bonds in Poland. The changes not only affected the legal provisions, but also the attitudes of self-government activists and institutions engaged in the issue of municipal bonds; hence, the organization of the market had to be different. As a consequence, a new bond market, GPW Catalyst, has been established on 30 September 2009.The paper aims at presenting the municipal bond market in Poland. The main aspects of this market that are significant for its development are identified. An analysis and assessment of the market’s development are conducted using the experience of more than a decade of developing the municipal bond market in Poland. The environment that led to the launching of the first municipal bond market in East-Central Europe at the end of 2009 is presented. The main motivation was the need to indicate new sources of finance during the periods of recession and the crisis of the public finance sector.